EFFECT OF IHSG, MONEY ALLOCATED, AND IMPORT VALUE ON VAT RECEIPT IN INDONESIA - Wijaya, Suparna; Utari Ayu Surinawa; Waidatin Nur Azizah (Dinasti Publisher, 2020)
Value Added Tax has a role that is quite large in state revenue. And the Composite Stock Price Index (IHSG) is a reflection of stock performance or good financial performance. If financial performance is good, sales and VAT will increase. Money supply reflects level of domestic consumption, if money supply rises, level of consumption increases, VAT will growth. Import value is a reflection of the import itself. If imports increase, the supply of goods from abroad to the country increases. If supply increases, consumption also increase, so VAT will grow. The purpose of this study was to examine the effect of IHSG, Money Supply, and Import Value on VAT receipts. The research method used is quantitative. The results showed that IHSG did not affect VAT receipts. Whereas Money Supply and Import Value have a significant influence on VAT receipts. However, IHSG, Money Supply, and Import Value simultaneously influence VAT revenue.